1995
DOI: 10.1097/00005373-199505000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Subarachnoid-Pleural Fistula

Abstract: Traumatic subarachnoid-pleural fistula was recently diagnosed in an 18-year-old male after a gunshot wound in the chest and spinal column. The diagnosis was suggested by persistent pleural drainage and headache in the setting of signs of spinal injury at the thoracic level. Computed tomographic myelography delineated the dural injury. The fistulous connection was defined and repaired at operation. This paper describes the diagnostic and therapeutic features encountered in the management of this rare disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Postoperative pneumocephalus could result from combination of a dural tear and a pneumorrhachis. An SAPF may remain asymptomatic when small, or may cause pleural effusion and subsequent dyspnea and pleuritic chest pain, in addition to postural headaches4579), nausea, and vomiting secondary to intracranial hypotension1). An SAPF once developed causes a pressure gradient, which allows cerebrospinal fluid (CSF) to flow from the positive-pressure spinal subarachnoid space to the negative-pressure pleural space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative pneumocephalus could result from combination of a dural tear and a pneumorrhachis. An SAPF may remain asymptomatic when small, or may cause pleural effusion and subsequent dyspnea and pleuritic chest pain, in addition to postural headaches4579), nausea, and vomiting secondary to intracranial hypotension1). An SAPF once developed causes a pressure gradient, which allows cerebrospinal fluid (CSF) to flow from the positive-pressure spinal subarachnoid space to the negative-pressure pleural space.…”
Section: Discussionmentioning
confidence: 99%
“…Another rare condition is a communication between the spinal subarachnoid space and pleural space after thoracic spine surgery. Pneumocephalus may manifest as severe headache4579) and acute neurologic changes that mimic brain metastasis, seizure, or stroke. However, the physiology and management of pneumocephalus are not widely recognized.…”
Section: Introductionmentioning
confidence: 99%
“…The first case was reported in 1959 by Milloy, et al 33 A search of Medline records revealed that since that first publication 54 cases have been reported. Thirty-seven were secondary to traumatic injury, [1][2][3][5][6][7][8]11,14,15,17,[20][21][22][23][24]26,29,30,[32][33][34][35][36][37][38][39][40][41][42]44,[47][48][49][50][51][52]55 and 15 to surgery. 4,9,10,12,13,16,19,25,27,28,34,43,45,...…”
Section: Discussionmentioning
confidence: 99%
“…In several reported cases, headache accompanied pleural effusion. 4,10,12,18,21 The headache is caused by two different mechanisms. If the parietal pleura is defective but the visceral pleura is intact, the pressure of the pleural space ranges from Ϫ5 to Ϫ7.5 cm H 2 O.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation